Influence of Work and Life Stressors on Marital Quality among Dual and Nondual Military Couples. (November 2020) - Woodall, Kelly A.; Richardson, Sabrina M.; Pflieger, Jacqueline C.; Hawkins, Stacy Ann; Stander, Valerie A.
Maintaining a healthy marriage may be challenging for military couples as they attempt to balance the demands of work and family; for dual-military couples, this can be even more challenging. Using data from the Millennium Cohort Family Study, we examined whether military stress experiences negatively impact marital quality through the mediation of work–family conflict. Spouse gender and dual-military status were included as moderators. Spouses reported on marital quality, work–family conflict, military stress experiences, and personal military experience. Spouse and service member demographics were also included. Results demonstrated that experiencing more military stress experiences was related to lower marital quality, which was mediated by work–family conflict. Additionally, female dual spouses reported lower marital quality than male dual spouses and civilian spouses. Findings from this study highlight the importance of providing support to military spouses for stressful military events and potentially tailoring support services for female dual spouses to improve marital quality.